Marketing the ‘Slippery’ Local with the Contrived ‘Rural’: Case Studies of Alternative Vegetable Retail in the Urban Fringe of Nagoya, Japan - Kingsbury, Aaron; Maeda, Yosuke; Takahashi, Makoto (The International Journal of Sociology of Agriculture and Food, 2010)
In recent years, a wealth of research has been conducted on alternative food economies and the construction of quality in markets in North America and Europe. Nonetheless, research undertaken from these perspectives on food networks in the Japanese context remains relatively unexplored. As the definition of quality is rooted in the social, political and economic contexts of particular places, understanding its construction requires empirical studies on actual alternative food economies in Japan. In efforts to partially address this gap, this article focuses on how re-embedded and possibly appropriated alternative food economies (re-)?valorize and then combine ‘locality’ with ‘rurality’ in farm product retail outlets in the Nagoya urban fringe. The authors conducted a series of interviews with retailers who source ‘locally’ produced vegetables from outside the Central Union of Agricultural Co-operatives to assess their goals, supply strategies and marketing images. The semantics of ‘local’ was found to be highly malleable based on retail imperatives, but its visualization through the photographic depiction of farmers was found to be a salient element in the construction and marketing of ‘quality’ to consumers.